Choosing cooperation over conflict: Russia and the Euro-Atlantic security order - Margarete Klein; Solveig Richter (Stiftung Wissenschaft und Politik (SWP), 2012)
With Putin once again taking the reigns as Russia's president, it can be expected that the country will become a difficult partner for the West over the coming years. For if one reads the articles and statements by Putin during the electoral campaign, it can be surmised that he will shape his foreign policy around anti-Western rhetoric and great power blustering. It is necessary, however, that there be continued efforts with Russia under Putin 3.0 in order to dampen the systemic conflict over political order. As long as it remains an unresolved issue as to how the Euro-Atlantic security order incorporating Russia should be shaped, it will not be possible to fully realize the amount of security policy cooperation with Moscow necessary to address current local and global security challenges. The Georgian War of 2008 emphatically demonstrated that the fragile relationship can worsen and take on crisis proportions as long as a stable system for cooperative security does not exist with Russia
Keywords: 320